Emergency rules to be followed for the resumption of the road cycling season in the context of the coronavirus pandemic - Barrio, J.; Bigard, X.; Boelens, A.; Cerfontaine, M.; Chaddot, R.; Clignet, M.; Jan, X.; Lopes, A.; Nash, K.; Sprouse, K.; Thouault, P.-Y. (2020)
The stakeholders of cycling and the UCI acknowledge the extraordinary nature of the COVID-19 pandemic and the ensuing difficulties for the organisation of safe sporting events. These are all the more acute in the context of cycling events due to the regular international travel, the use of free-access venues and facilities and the different team and staff compositions. In consideration of these extraordinary circumstances, the UCI and stakeholders of cycling agreed to constitute the UCI Steering Group to present to the UCI Management Committee a set of emergency rules with the objective of reducing the risk of transmission of the coronavirus during events of the UCI International Calendar. The UCI would like to thank the members of the working group for their contribution. The listed contributors served to provide advice and opinions as the UCI has navigated this difficult issue. Ultimately, the UCI has had to make final decisions on the topics contained in this document, and this should not been as a "consensus statement", per se.Upon agreement within the UCI Steering Group, these Rules were presented to and approved by the UCI Management Committee in accordance with article 47.1 lit. k) of the UCI Constitution. The Rules include requirements, instructions (mandatory measures) and presentrecommendations for good practice (recommended and desired measures) for organising cyclingevents during the COVID-19 pandemic. The Rules apply to all UCI Class 1 and Class 2 events. The Rules apply to all Events taking place as of approval by the UCI Management Committee until they are repealed by the UCI Management Committee and no earlier than 31 December 2020. The Management Committee has instructed the UCI Steering Group to update the present Rules on a regular basis in consideration of new knowledge and progress in the field of biotechnology, especially for COVID-19 testing. Any amendments shall be published without delay and shall be immediately applicable, unless indicated otherwise. A consolidated version containing the latest amendments in force will be published on the dedicated webpage of the UCI website as soon as practicable: https://www.uci.org/road/news/2020/covid-19-pandemic-how-to-return-to-cycling-events The document is divided into two main sections, a section concerning risk assessment, and a section setting out the requirements and practical recommendations to be implemented by organisers and teams in relation to the Events.